2005
DOI: 10.1007/s00299-005-0930-3
|View full text |Cite
|
Sign up to set email alerts
|

Plastid transformants of tomato selected using mutations affecting ribosome structure

Abstract: Tomato plastid transformants were obtained using two vectors containing cloned plastid DNA of either Nicotiana tabacum or Solanum nigrum and including point mutations conferring resistance to spectinomycin and streptomycin. Transformants were recovered after PEGmediated direct DNA uptake into protoplasts, followed by selection on spectinomycin-containing medium. Sixteen lines contained the point mutation, as confirmed by mapping restriction enzyme sites. One line obtained with each vector was analysed in more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Homoplasmy, as established by molecular analyses and germination of progeny seeds on antibiotic-containing medium, was achieved directly on the primary regenerants without the need for multiple rounds of selection/regeneration, confirming results previously reported (Kavanagh et al 1999;Nugent et al 2005). Homoplasmic shoots were produced in about 4-5 months, which is comparable with the time required by the biolistic approach with ''inactivatingtype'' vectors, considering the repeated regeneration cycles on selective medium necessary to achieve homoplasmy.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Homoplasmy, as established by molecular analyses and germination of progeny seeds on antibiotic-containing medium, was achieved directly on the primary regenerants without the need for multiple rounds of selection/regeneration, confirming results previously reported (Kavanagh et al 1999;Nugent et al 2005). Homoplasmic shoots were produced in about 4-5 months, which is comparable with the time required by the biolistic approach with ''inactivatingtype'' vectors, considering the repeated regeneration cycles on selective medium necessary to achieve homoplasmy.…”
Section: Discussionsupporting
confidence: 88%
“…The frequent homologous recombinations during plastid DNA transformation (Kavanagh et al 1999) may also decrease the co-integration frequency of the resistance mutation and the transgene. Nevertheless, it has been used in several instances with different Nicotiana genotypes (Golds et al 1993;O'Neill et al 1993;Kavanagh et al 1999;Horváth et al 2000;Rumeau et al 2004;Buhot et al 2006) and also with tomato (Nugent et al 2005), exploiting either homologous or homeologous recombination for transgene integration.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, no apparent reductions in transformation frequencies were observed in tobacco and tomato using homologous or homeologous N. tabacum and S. nigrum ptDNA sequences in transformation vectors (Kavanagh et al 1999;Horváth et al 2000;Nugent et al 2005;Nugent et al 2006), or in transformations of N. benthamiana plastids with tobacco-derived vectors (Davarpanah et al 2009), indicating that species-specific vectors are not always necessary. In the tobacco and tomato studies, it was demonstrated that integration of the cloned homeologous ptDNA sequences in the host plastome occurred by multiple recombination events in a similar region of the inverted repeats (IRs), that in comparison with ''Single Copy'' regions of the plastid genome, generally show a higher gene order conservation and a lower sequence divergence (Maier et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In tobacco and tomato, plastid transformation is most commonly achieved by biolistic delivery of DNA into leaf explants (e.g. [23,11]), but has also been achieved via direct DNA uptake into protoplasts [24,25,1]. In species other than tobacco, adventitious shoot regeneration from bombarded leaf or petiole explants typically leads to a high number of spontaneous spectinomycin resistant mutants, with a smaller number of plastid transformants [11,[15][16][17][18], and transformation frequencies are in general much lower than in tobacco.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, plastid transformants have been produced in a growing number of species including potato [9,10], tomato [1,11], carrot [12], soybean [13], cotton [14], petunia [15] and several members of the Brassicaceae including Arabidopsis thaliana [16], Brassica napus [17] and Lesquerella fendleri [18]. In addition, several promising methods for marker gene excision or generation of marker-free plants from plastid-transformed plants have been demonstrated in tobacco [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%